Architectural and urban transformations of large housing estate related to functional diversification: case of Kelenföld in Budapest - Antypenko, Hlib; Benkő, Melinda (Journal of Architecture and Urbanism, 2022)
Large housing estates (LHEs) is a global product of modern planning and architecture based on the concept of the functional city. However, during the last decades, these inherited mass housing neighborhoods have been gradually transformed in their social and physical context. Much of this change is due to functional diversification of LHEs following rising consummation demands. The objective of the research is to create a general simple typology discovering this phenomenon and providing a method to make case study analysis and comparative studies. How to classify functional diversification and morphological transformations in LHEs in general? What are the functional and morphological values that were preserved from modern development period and what are the new characteristics of contemporary transformations? What are the special characteristics of the functional diversification in a post-socialist city? Kelenföld case study from Budapest is introduced to test the typology by using local documents and fieldwork methods in architecture: mapping, morphological analysis, and photo making. Kelenföld is one of the best located and the first LHE in Budapest realized with large panel technology in the 60’s, being today intensively developed and favored by its users.